IL‐20 promotes cutaneous inflammation and peripheral itch sensation in atopic dermatitis. Issue 6 (29th April 2022) - Lu, Zhiping; Xiao, Song; Chen, Weiwei; Zhu, Renkai; Yang, Hua; Steinhoff, Martin; Li, Yanqing; Cheng, Wenke; Yan, Xinrong; Li, Lianlian; Xue, Shanghai; Larkin, Ciara; et al.
Abstract: Atopic dermatitis (AD) is a chronic skin disease, which is associated with intense itch, skin barrier dysfunction and eczematous lesions. Aberrant IL‐20 expression has been implicated in numerous inflammatory diseases, including psoriasis. However, the role of IL‐20 in AD remains unknown. Here, RNA‐seq, Q‐PCR, and immunocytochemistry were utilized to examine disease‐driven changes of IL‐20 and its cognate receptor subunits in skin from healthy human subjects, AD patients and murine AD‐models. Calcium imaging, knockdown and cytokine array were used to investigate IL‐20‐evoked responses in keratinocytes and sensory neurons. The murine cheek model and behavioral scoring were employed to evaluate IL‐20‐elicited sensations in vivo. We found that transcripts and protein of IL‐20 were upregulated in skin from human AD and murine AD‐like models. Topical MC903 treatment in mice ear enhanced IL‐20R1 expression in the trigeminal sensory ganglia, suggesting a lesion‐associated and epidermal‐driven mechanism for sensitization of sensory IL‐20 signaling. IL‐20 triggered calcium influx in both keratinocytes and sensory neurons, and promoted their AD‐related molecule release and transcription of itch‐related genes. In sensory neurons, IL‐20 application increased TLR2 transcripts, implicating a link between innate immune response and IL‐20. In a murine cheek model of acute itch, intradermal injection IL‐20 and IL‐13 elicited significant itch‐like behavior, though only when co‐injected. Our findings provide novel insights into IL‐20 function in peripheral (skin‐derived) itch and clinically relevant intercellular neuron‐epidermal communication, highlighting a role of IL‐20 signaling in the pathophysiology of AD, thus forming a new basis for the development of a novel antipruritic strategy via interrupting IL‐20 epidermal pathways.